The major Industry and its technique in Japan - Hoynden, Yoshio (Economic Co-opertion, 1954)
This book introduce the coal mining industry, the non-ferrous metal industry, thw iron and steel industry, the shipbuilding industry, the machinery industry, the chemical industry...